Analisis Pengaruh Strategi Manajemen Operasional terhadap Perawatan Warehouse - Daniel David Camberra Simanungkalit (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Warehouse management and internal logistics planning and control are increasingly important. Nowadays, many Warehouse management methods as well as internal logistics planning and control are increasingly important. Warehouses play a critical role in matching product demand with supply at various echelons in the supply chain. The warehouse decision model is very important for the profitability of an organization. The method used in this research activity uses a qualitative approach where this approach explores and understands the meaning of some individuals or groups of people who originate from social problems. warehouse layout arrangements, inventory arrangements, maintenance of warehousing equipment, storage of goods, stock lists, entry of goods, expenditure of goods, picking of goods, packaging of goods, delivery of goods, and so on. Benefits of implementing good warehouse management, such as: 1. Serving customers better 2. Obtaining data in real time 3. Preventing the risk of loss 4. Avoiding fraud 5. More accurate reordering of goods. Suggestions for further research, adding another subject to understand warehouse design what it is like and how to manage it.